1971
DOI: 10.1073/pnas.68.8.1748
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Immunization with Mouse Fetal Antigens on Growth of Cells Infected with Rauscher Leukemia Virus and on Plasma-Cell Tumors

Abstract: The recovery of spleen cells infected with Rauscher leukemia virus (RLV) and grown in Millipore diffusion chambers, the development of RLV-induced splenomegaly, and the cumulative mortality from a transplanted ascites plasma-cell tumor were all suppressed in young adult BALB/c male mice previously primed at 3-weekly intervals with x-irradiated, syngeneic Numerous reports have suggested that fetal cells have antigens that cross-react with specific transplantation antigens in tumor cells (1-6). Although the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In our experiments a strain-dependent sensitivity to anti-embryo immunization might have interfered as indicated by Ting et al (1973~) who were able to induce an anti-embryo immunity in C57BL and C3H but not in BALB/c mice. I t has been shown, however, that antiembryo immunity can he effectively evoked in BALB/c mice (Hanna et al, 1971 ;Salinas et al, 1972). The difficulty of obtaining anti-embryo antibodies in the BALB/c strain reported by Ting et al (1973~) may be ascribed to the use of embryos taken from non-primiparous females, since primiparous animals seem to provide embryos with the highest immunogenic properties (Coggin et ul., 1971;Girardi et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments a strain-dependent sensitivity to anti-embryo immunization might have interfered as indicated by Ting et al (1973~) who were able to induce an anti-embryo immunity in C57BL and C3H but not in BALB/c mice. I t has been shown, however, that antiembryo immunity can he effectively evoked in BALB/c mice (Hanna et al, 1971 ;Salinas et al, 1972). The difficulty of obtaining anti-embryo antibodies in the BALB/c strain reported by Ting et al (1973~) may be ascribed to the use of embryos taken from non-primiparous females, since primiparous animals seem to provide embryos with the highest immunogenic properties (Coggin et ul., 1971;Girardi et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by several authors that cells of tumors induced by viruses may share antigens with embryos (Pearson and Freeman, 1968;Coggin et al, 1970;Hanna et al, 1971; Ting et al, 1972). While this has been established by using in vitro techniques (Pearson and Freeman, 1968;Ting et al, 1972;Berman, 1972;Girardi et al, 1973); in vivo transplantation methods have yielded conflicting results (Ting, 1968;Coggin et al, 1971 ;Ting et al, 1972;Ting et al, 19736).…”
Section: Transplantation Of Mca-i Sarcoma Cells Immunization With Symentioning
confidence: 99%
“…A number of groups have reported that immunization with foetal tissue is ineffective as a means of inducing tumour-immunity (Pearson and Freeman, 1968;Ting, 1968;Basombrio and Prehn, 1972). In contrast to this, several workers, using SV40-induced tumours (Coggin, Ambrose and Anderson, 1970) and Rauscher-leukaemia-virus-induced tumours (Hanna, Tennant and Coggin, 1971) have suggested that foetal immunization can confer tumour immunity. Perhaps even more striking are the examples where foetal immunization has been shown to enhance the growth of tumours expressing embryo-associated antigens (Castro et al, 1973;Parmiani and Lembo, 1974).…”
mentioning
confidence: 95%
“…The contribution of these tumor-associated fetal antigens in eliciting effective antitumor immune responses is controversial. In the past, deliberate fetal immunization has had no effect [5,44,66], a protective effect [12,26,46,52] or even a stimulating effect [8,42] on syngenic tumor cell growth. Recent studies have suggested that tumor-associated fetal antigens on fetal cells are immunoprotective [24,27] and can induce a T cell response in vivo against even weakly antigenic metastatic tumors [18].…”
Section: Discussionmentioning
confidence: 99%